Mentoring to cultivate female talent in science - Gómez-Navarro, Cristina; Hansen, Julia (FEBS letters, 2025)
Women in science face external barriers and internal challenges, such as the ‘stereotype threat’, which can lead to self-limiting practices. To help students overcome these, Cristina Goméz-Navarro, a professor and member of the gender equality commission at IFIMAC Madrid, set up a female mentoring program. Here, she outlines objectives and cornerstones of this program, unexpected outcomes, and tips for others who plan to set up similar systems.
Gesehen am 27.01.2026